2014
DOI: 10.1074/jbc.m114.548669
|View full text |Cite
|
Sign up to set email alerts
|

Bisretinoid-mediated Complement Activation on Retinal Pigment Epithelial Cells Is Dependent on Complement Factor H Haplotype

Abstract: Background: AMD and STGD1 are blinding diseases with similar clinical presentations but unrelated genetic causes. Results: Bisretinoid-dependent complement reactivity on RPE cells involves the alternative pathway and depends on the CFH haplotype. Conclusion: Inefficient CFH synthesis because of either Y402H and I62V substitutions or bisretinoid accumulation predisposes RPE cells to disease. Significance: These results suggest a common inflammatory etiology for AMD and STGD1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 46 publications
1
26
0
Order By: Relevance
“…To date, the triggers or immunogens for complement activation are not known. However, using in vitro and animal models, several groups have shown that dimers of vitamin A, such as A2E, may activate complement (33)(34)(35). Our data demonstrate that inhibiting dimerization by C20-D 3 -vitamin A normalizes the transcriptional dysregulation of complement components.…”
Section: Discussionsupporting
confidence: 51%
“…To date, the triggers or immunogens for complement activation are not known. However, using in vitro and animal models, several groups have shown that dimers of vitamin A, such as A2E, may activate complement (33)(34)(35). Our data demonstrate that inhibiting dimerization by C20-D 3 -vitamin A normalizes the transcriptional dysregulation of complement components.…”
Section: Discussionsupporting
confidence: 51%
“…CFH is a soluble CRP secreted by liver and RPE cells (33). Notably, complement activation in bisretinoid-laden RPE cells has been shown to be strongly dependent on the CFH haplotype (34). Moreover, a subset of AMD has been linked to ABCA4 mutations, suggesting a…”
mentioning
confidence: 99%
“…In fact, recent studies using both mouse- (13) and porcine-derived (14) RPE have demonstrated that RPE cells in culture are capable of forming basal deposits in a cell-autonomous fashion. Furthermore, human fetal RPE (hfRPE) cultures, when exposed to exogenous stressors such as serum (15) or POS (16), have been shown to develop drusen-like basal deposits. However, the ability of cultured human RPE obtained from a macular degeneration patient, in the absence of any exogenous stressors, to develop drusen, has not been investigated.…”
mentioning
confidence: 99%